(untitled) (Medical Forum Monthly, 2024)
Objective: To determine frequency of modifiable risk factors about coronary artery disease in an urban female population of Sargodha city of Punjab province of Pakistan. Study Design: Descriptive / cross sectional study. Place and Duration of Study: This study was conducted at the urban female population of Sargodha city of Punjab province of Pakistan from March, 1st to 30th 2016. Materials and Methods: This study was carried out to identify frequency of modifiable risk factors about coronary artery disease in an urban female population of Sargodha city. All 100 married female apparently healthy participants; 25-60 years of age were included. Results: The mean age of subjects was 36.02±10.02 years. The frequency of smoking (27%) was expressively advanced in study population, sedentary lifestyle (19%) obesity (25%), use of salt (16%) and use of fat (13%) respectively. Conclusion: The current research concludes a reduced information related to modifiable threat aspects regarding coronary artery disease in the urban feminine populace. Consequently, there is a speedy prerequisite to initiate actions to educate peoples of this group in relation of changeable risk features so that those at high risk for upcoming patients of controllable coronary artery disease can be coped.